Internal Audit and Governance Practices: Their Impact on the Performance of Water Services Regional-Owned Enterprises (BUMDs) in Indonesia - Hana Aulia Diany; Hidayatullah (PT. Altaf Publishing Corp, 2025)
Water Services Regional-Owned Enterprises (BUMD Jasa Air) are entities owned by local governments that function to provide clean water to communities within their service areas. The objective of this study is to examine the effectiveness of corporate governance implementation, the number of internal audit unit personnel, and the number of company employees on the performance evaluation results of these enterprises. This research adopts a quantitative approach using secondary data. The population consists of 394 water utility BUMDs during the period from 2021 to 2023, while the sample was determined using purposive sampling, resulting in 22 BUMDs that met the research criteria. The analytical methods used include descriptive statistical analysis, classical assumption testing, and panel data regression model selection tests to test the hypotheses. The results indicate that the three independent variables collectively have a significant effect on the dependent variable. Corporate governance implementation, the number of internal audit personnel, and the number of employees all show a positive relationship with the performance evaluation results of water utility BUMDs. Specifically, corporate governance has a positive and significant effect; the number of internal audit personnel shows no significant effect; and the number of employees has a positive but not statistically significant impact on performance evaluation.